Multimodal imaging of the amygdala in non-clinical subjects with high vs. low autistic-like social skills traits - Zovetti, Niccolò; Meller, Tina; Evermann, Ulrika; Pfarr, Julia-Katharina; Hoffmann, Jonas; Federspiel, Andrea; Walther, Sebastian; Grezellschak, Sarah; Jansen, Andreas; Abu-Akel, Ahmad; Nenadić, Igor (Psychiatry research. Neuroimaging, 2025)
•Autistic-like social skills are associated with altered amygdala blood flow.•Right amygdala activation to emotional faces differed in high vs low social skills.•Autistic-like traits were not associated with amygdala functional connectivity. Recent clinical and theoretical frameworks suggest that social skills and theory of mind impairments characteristic of autism spectrum disorder (ASD) are distributed in the general population on a continuum between healthy individuals and patients. The present multimodal study aimed at investigating the amygdala's function, perfusion, and volume in 56 non-clinical subjects from the general population with high (n = 28 High-SOC) or low (n = 28 Low-SOC) autistic-like social skills traits. Participants underwent magnetic resonance imaging to evaluate the amygdala's functional connectivity at rest, blood perfusion by means of arterial spin labelling, its activation during a face evaluation task and lastly grey matter volumes. The High-SOC group was characterised by higher blood perfusion in both amygdalae, lower volume of the left amygdala and higher activations of the right amygdala during processing of human faces with fearful value. Resting state analyses did not reveal any significant difference between the two groups. Overall, our results highlight the presence of overlapping morpho-functional alterations of the amygdala between healthy individuals and ASD patients confirming the importance of the amygdala in this disorder and in social and emotional processing. Our findings may help disentangle the neurobiological facets of ASD elucidating aetiology and the relationship between clinical symptomatology and neurobiology.